Analisis Keterkaitan Karakter Nilai Integritas Siswa Terhadap Motivasi Belajar Siswa Kelas VIII Pada Mata Pelajaran PPKn di Smp Negeri 1 Muaro Jambi - Irwan; Indra Sabdarudin; Sariani, Dona (Civic Education Perspective Journal, 2022)
Based on the results of initial observations that have been made by class VIIIstudents of SMP Negeri 1 Muaro Jambi, it shows several problems regarding studentmotivation in the medium category and student activities in the school environment whichcan be said to be regulations in the form of bringing motorbikes to school, hanging outoutside class when the teacher does not come in, the dishonesty of students whentransacting with traders at school and the class atmosphere is not conducive when theteacher is not in.The purpose of this study was to determine the relationship of the character of the integrityvalue of students to the learning motivation of class VIII students in Civics subjects at SMPNegeri 1 Muaro Jambi.This study uses qualitative data collection methods in the form of observation,questionnaires, interviews and documentation. Data analysis techniques in this study weredescriptive and qualitative descriptive statistics. This research was carried out in 3 stages,namely the pre-field stage in October to November 2021, the field work stage in December2021 to January 2022 and the data analysis stage in February to month March 2022. Theinformants in this study consisted of 10 grade VIII students and 2 PPKn teachers.The results of this study indicate that out of 10 grade VIII students of SMP Negeri 1 MuaroJambi, only 2 people have the character of integrity values. These 2 people consist ofstudents with very high learning motivation and students with moderate learningmotivation. The 8 students who do not yet have the character of the complete integrityvalue consist of students who have very high learning motivation, high learning motivationand low learning motivation.The conclusion in this research is that students who have high or even very highmotivation do not rule out the possibility that these students have integrity withinthemselves. This is because students are only pegged to get good grades, so they justifyprohibited methods to get good grades. In addition, the lack of self-awareness of theimportance of a healthy process or struggle in order to get maximum results also makesstudents not care about what they are doing wrong or right.